RECONSTRUCTION OF THE FAMILY LAW PARADIGM IN AN EFFORT TO MEASURE THE POLITICAL AWARENESS OF COMMUNITY LAW: Rekonstruksi Paradigma Hukum Keluarga Dalam Upaya Menakar Kesadaran Politik Hukum Masyarakat - M. Mutamakin; Ansari Ansari (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
The presence of Islamic family law is beneficial for all residents of Indonesia, as it covers all matters related to marriage, divorce procedures, child maintenance, polygamy, and others. This study uses the literature method to provide data on philosophical value in family law reconstruction and evaluate society's level of legal awareness. The research method used is descriptive analysis, an approach in legal philosophy based on the theory of legal awareness and the provision of complete information. The results showed that Islam is the main factor that regulates various aspects of social life. Furthermore, the social changes that occurred during the time of Umar's caliphate impacted the spread of Islamic political doctrine and the emergence of several issues of Islamic law. Third, intellectuals are free, so their mastery of political Islam can be expanded through legal interpretations based on their views. Then, the power can quickly grow by taking advantage of the opportunities that arise over time.